TOKENS IN INTERNATIONAL TRADE: ACCOUNTING IDENTIFICATION OF DIGITAL ASSETS AND TAX BASE FRAGMENTATION (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article is devoted to the study of the role of tokens and digital assets in the transformation of international trade. An approach to the accounting identification of digital assets and the classification of tokens into those that provide access to services, as well as those that have or do not have economic benefits, is substantiated, which allows reducing the fragmentation of the tax base and enhancing the consistency of accounting and taxation in cross-border transactions.
Keywords: tokens; digital assets; accounting identification; international trade; accounting; tax base fragmentation; taxation of digital assets; tokenization; IFRS; cross-border transactions